Tele-pharmacy in rural Scotland: a proof of concept study. (2nd May 2017) - Inch, Jackie; Notman, Frances; Watson, Margaret; Green, David; Baird, Robert; Ferguson, James; Hind, Caroline; McKinstry, Brian; Strath, Alison; Bond, Christine
Abstract: Introduction: Technology enables medical services to be provided to rural communities. This proof of concept study assessed the feasibility and acceptability of delivering community pharmacy services (CPS; including advice, sale of over-the-counter products and dispensing of prescriptions) by tele-technology (the Telepharmacy Robotic Supply Service (TPRSS)) to a rural population in Scotland. Methods: Data collection included the following: postal surveys to local residents; focus groups/ interviews with pharmacists, other healthcare professionals (HCPs) and service users, at baseline and follow-up; TPRSS logs. Interviews/focus groups were audio-recorded, transcribed and thematically analysed. Descriptive statistics were reported for survey data. Results: Qualitative results: Pre-installation: residents expressed satisfaction with current pharmacy access. HCPs believed the TPRSS would improve pharmacy access and reduce pressure on GPs. Concerns included costs, confidentiality, patient safety and 'fear' of technology. Post-installation: residents and pharmacy staff were positive, finding the service easy to use. Quantitative results : Pre-installation: almost half the respondents received regular prescription medicines and a third used an over-the-counter (OTC) medicine at least monthly. More than 80% (124/156) reported they would use the TPRSS. There was low awareness of the minor ailment service (MAS; 38%; 59/156). Post-installation: prescription ordering and OTC medicine purchase were used most frequently; the video link was used infrequently. Reasons for non-use were lack of need (36%; 40/112) and linkage to only one pharmacy (31%; 35/112). Discussion: Community pharmacy services delivered remotely using tele-technology are feasible and acceptable. A larger study should be undertaken to confirm the potential of the TPRSS to reduce health inequalities in rural areas.